2009
DOI: 10.1021/jp904330v
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Induced Denaturation Process on Defatted Human Serum Albumin and in the Presence of Palmitic Acid

Abstract: We report a study on the unfolding behavior of the most abundant protein contained in plasma, human serum albumin. The unfolding mechanisms in denaturing conditions induced by urea are studied for the defatted form (HSA) and for the palmitic acid:albumin (HSAPalm) complex. We employed the singular value decomposition method to determine the minimum number of structural states present in the unfolding processes. Low-resolution three-dimensional structures are reconstructed from the one-dimensional small-angle X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 67 publications
8
48
0
Order By: Relevance
“…For DF-HSA the helix content falls from 54% to about 37% . This resultis consistent with the denaturation results of Leggio et al [15]that the fatty acids in F-HSA confer structural stability and hence resistance to nanoparticle-induced denaturation and the conformation changes of human hemoglobin seen on silica [16].…”
Section: Protein Secondary Structure Changessupporting
confidence: 93%
“…For DF-HSA the helix content falls from 54% to about 37% . This resultis consistent with the denaturation results of Leggio et al [15]that the fatty acids in F-HSA confer structural stability and hence resistance to nanoparticle-induced denaturation and the conformation changes of human hemoglobin seen on silica [16].…”
Section: Protein Secondary Structure Changessupporting
confidence: 93%
“…By comparing the interpretation of the spectroscopic and the scattering data of the HSAIbu system with the results obtained for the free HSA defatted solutions 21 it was clear that in the case of the HSAIbu, the unfolding process takes place later on the denaturant concentration scale. Indeed, we observed that the HSA binding ibuprofen molecules remained in the native form up to a limit urea concentration of 3.90 M. This limit value is higher than the one reported for HSA (2.50 M).…”
Section: Discussionmentioning
confidence: 88%
“…21 A very detailed analysis of SAXS, DLS, CD and fluorescence was carried out. In particular, the SVD analysis and the three-dimensional reconstructions allowed the determination of number, percentage and low resolution structures of the conformers involved in the unfolding process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations